Analisis Faktor Yang Memengaruhi Kejadian Hipertensi Pada Lansia Di Poli Penyakit Dalam RSUD Dr.R.M.Djoelham Binjai - Debri Aji Pratama (Pusat Riset dan Inovasi Nasional, 2023)
According to the American Heart Association or AHA, hypertension is a silent killer, with symptoms that can vary from individual to individual and are almost the same as symptoms of other diseases. Hypertension is a risk factor for various cardiovascular diseases and stroke. According to the AHA, hypertension is a disease that occurs due to an increase in systolic blood pressure> 140 mmHg or diastolic blood pressure> 90 mmHg. This type of research uses a descriptive analytic survey with a cross sectional design. The population in this study were all elderly (≥60 years) hypertensive patients at the Internal Medicine Polyclinic totaling 156 people, while the sample numbered 156 people by means of total sampling. Data analysis was performed using univariate, bivariate and multivariate analysis. Based on the results of the chi-square test it is known that the incidence of hypertension affects smoking, obesity, low-fiber diet, excessive salt consumption and lack of physical activity p = 0.000, meaning that there is an effect of smoking, obesity, low-fiber diet, excessive salt consumption and lack of physical activity on hypertension incident. From the results of multivariate analysis it is known that the most influential variable in this study is obesity with an OR value of 62,850. The conclusion in this study is that obesity is the dominant factor influencing the incidence of hypertension in the Internal Medicine Polyclinic at Dr.R.M.Djoelham Binjai Hospital. In order to reduce the prevalence of hypertension, it is hoped that the Patients of the Internal Medicine Polyclinic at Dr, R.M.Djoelham Binjai Hospital will apply hypertension management with a healthy lifestyle so that diabetics can have controlled blood pressure levels.